Analysis of the regulation on renewable energy, distributed generation and smart grids in the Argentine electrical industry with a look at the sustainable development goals (SDGs) - Aquino, Camila (2025)
Fil: Aquino, Camila. Universidad Nacional de Misiones. Facultad de Ciencias Económicas; Argentina.